2021
DOI: 10.3390/coatings11121433
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Bioceramic Coatings on the Surface of Ti–6Al–4V Alloy by Plasma Electrolytic Oxidation Followed by Gas Detonation Spraying

Abstract: In this work, bioceramic coatings were formed on Ti6Al4V titanium alloy using a combined technique of plasma electrolytic oxidation followed by gas detonation spraying of calcium phosphate ceramics, based on hydroxyapatite. Plasma electrolytic oxidation was carried out in electrolytes with various chemical compositions, and the effect of electrolytes on the macro and microstructure, pore size and phase composition of coatings was estimated. Three types of electrolytes based on sodium compounds were used: phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…It can be emphasized here that Ohki et al [34] also noted the absence of harmful CaO compound in HA coatings obtained by thermal spraying. Moreover, Rakhadilov and Baizhan [35] note the presence of characteristic sharp HA peaks on the HA coating diffraction patterns, along with the absence of CaO, which demonstrates good crystallinity of the HA phase of the coating obtained by gas detonation spraying of HA powder on the surface of Ti-6Al-4V alloy. Results of the authors' previous scientific study [26] showed the same results as in this study for the values of purity and crystallinity of the microplasmasprayed HA coating on a pure titanium sublayer.…”
Section: Resultsmentioning
confidence: 90%
“…It can be emphasized here that Ohki et al [34] also noted the absence of harmful CaO compound in HA coatings obtained by thermal spraying. Moreover, Rakhadilov and Baizhan [35] note the presence of characteristic sharp HA peaks on the HA coating diffraction patterns, along with the absence of CaO, which demonstrates good crystallinity of the HA phase of the coating obtained by gas detonation spraying of HA powder on the surface of Ti-6Al-4V alloy. Results of the authors' previous scientific study [26] showed the same results as in this study for the values of purity and crystallinity of the microplasmasprayed HA coating on a pure titanium sublayer.…”
Section: Resultsmentioning
confidence: 90%
“…High porosity is observed in all samples. The presence of pores is favorable for the ingrowth of bone tissue in them and the formation of a stronger connection of the implant with the bone [4]. In order to confirm and coordinate the obtained optical microscopy data, it is necessary to additionally conduct scanning electron microscopy studies and X-ray spectral analysis, the results of which are planned to be published by the authors in the following papers.…”
Section: Research Resultsmentioning
confidence: 99%
“…The MAO method in aqueous solutions of electrolytes has become widespread in the last decade as a method of applying bioactive CF coatings to the surface of titanium [4]. The coating formation in a microarc discharge is associated with the course of high-temperature chemical processes in the zone of local micro-plasma and micro-arc discharges under the influence of an external high voltage source and is associated with the oxidation of the base material, as well as the transition of the ultrafine phase in the electrolyte into the coating.…”
Section: Introductionmentioning
confidence: 99%
“…During detonation combustion of a mixture of gases, propane and oxygen, the powder particles are affected by elevated temperatures, pressures and acceleration. The calculated temperature in the channel reaches 3000 K and the pressure is 5 MPa [22,23]. At the beginning of the process, the gas powder cloud reaches a velocity of 1500 m/s, and then slightly melted powder particles are moved to the substrate at a velocity of up to 1000 m/s.…”
Section: Methodsmentioning
confidence: 99%